One thousand plant transcriptomes and the phylogenomics of green plants - Leebens-Mack, James H.; Große, Ivo; Porsch, Martin; Quint, Marcel; Koch, Marcus (Nature, 2019)
The One Thousand Plant Transcriptomes Initiative provides a robust phylogenomic framework for examining green plant evolution that comprises the transcriptomes and genomes of diverse species of green plants.